IWMI & CEEW Study: Integrating Food, Land, and Water for Poverty Reduction in Odisha - Bhaduri, Tanmoy; Mitra, Archisman; Taneja, Garima (CGIAR, 2023)
International Water Management Institute (IWMI) and the Council on Energy, Environment and Water (CEEW) organized a state consultation workshop on 14 December 2023 on ‘Policy Coherence in Food, Land, and Water (FLW) Systems: A case study of Odisha’ at Bhubaneswar as a part of the CGIAR Research Initiative on National Policies and Strategies Initiatives (NPS). The Food, Land and Water (FLW) project aims to identify key state-level policies in the food, land, and water systems that have a practical scope for improving coherence and hold most potential for creating an impact. The workshop was organized in partnership with the Department of Agriculture and Farmers’ Empowerment, Government of Odisha.